EFL STUDENTS’ EXPERIENCE IN LEARNING SPEAKING ENGLISH WITH PECHA KUCHA PRESENTATION ACTIVITY - Widya Garini Garini; Maman Suryaman (PROJECT (Professional Journal of English Education), 2022)
Students' English speaking ability is one of the important skills for EFL students to master. In mastering these speaking skills, students are given innovative and creative learning methods in the classroom so that learning objectives are achieved. The learning method for speaking English that will be taught in this study is the Pecha Kucha presentation method. This article will discuss how the students experience while learning English speaking in the classroom by the teacher using a learning method with a presentation format called Pecha Kucha. In addition, the obstacles experienced by students while learning to speak English in the classroom will also be discussed in this study. Through narrative inquiry research, students' experiences will be told in depth so that research questions are reached. The important result of this research shows that students have several obstacles in speaking English in class such as fear of making mistakes, lack of vocabulary to nervousness. Students also have a positive response to the use of Pecha Kucha as a learning method in their English speaking class. Students also stated that they prefer the Pecha Kucha presentation format which focuses on the presenter rather than just reading the presentation slides as in the old presentation format. The interpretation of the results for this study will be more in-depth, complemented by student voices through questionnaires and semi-structured interviews. Keywords:  EFL Students, Speaking English, Experience, Pecha Kucha Presentation